2018
DOI: 10.3390/molecules23071795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tea Catechins on Influenza Infection and the Common Cold with a Focus on Epidemiological/Clinical Studies

Abstract: Influenza and the common cold are acute infectious diseases of the respiratory tract. Influenza is a severe disease that is highly infectious and can progress to life-threating diseases such as pneumonia or encephalitis when aggravated. Due to the fact that influenza infections and common colds spread easily via droplets and contact, public prevention measures, such as hand washing and facial masks, are recommended for influenza prophylaxis. Experimental studies have reported that tea catechins inhibited influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 41 publications
0
40
0
3
Order By: Relevance
“…Regular consumption of green tea has been shown to decrease influenza infection and some cold symptom rates. In addition, gargling with tea catechins protects against influenza infection and common cold [49]. A study has also shown that consuming green tea supplements twice daily for 3 months resulted in a significant decrease in cold or influenza symptoms by approximately 23%.…”
Section: Catechinsmentioning
confidence: 99%
“…Regular consumption of green tea has been shown to decrease influenza infection and some cold symptom rates. In addition, gargling with tea catechins protects against influenza infection and common cold [49]. A study has also shown that consuming green tea supplements twice daily for 3 months resulted in a significant decrease in cold or influenza symptoms by approximately 23%.…”
Section: Catechinsmentioning
confidence: 99%
“…Last three decades several studies suggested that the regular consumption of green tea decreases influenza infection and some cold symptoms. The gargling with tea extracts and/or flavonoids may protect from influenza virus [18]. EGCG-fatty acid derivative is important because fatty acid on the phenolic hydroxyl group increase viral and cellular membrane permeability which protects from viral infection [19].…”
Section: Introductionmentioning
confidence: 99%
“…Mehrere epidemiologische Studien haben gezeigt, dass der regelmäßige Verzehr von grünem Tee die Influenza-Infektionsrate senkt [4]. In klinischen Studien wurden meist standardisierte Katechinextrakte verwendet.…”
Section: Grünteeunclassified